2016
DOI: 10.1002/smll.201602469
|View full text |Cite
|
Sign up to set email alerts
|

Shape Controlled Plasmonic Sn Doped CdO Colloidal Nanocrystals: A Synthetic Route to Maximize the Figure of Merit of Transparent Conducting Oxide

Abstract: The synthesis of different anisotropic shaped (eight different shapes) Sn doped CdO (Sn:CdO) colloidal nanocrystals (NCs) by precise tuning of precursor reactivity and proper choice of capping agent is reported. In all these systems, formation of Sn:CdO quantum dots (QDs) of 2-3 nm is identified at very early stage of reaction. The colloidally stable QDs act as a continuous source for the formation of primary nanoparticles that can be transformed selectively into specific type of nanoparticle morphology. The s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(40 citation statements)
references
References 59 publications
2
38
0
Order By: Relevance
“…Similarly, a small change in growth temperature can also change the crystallite orientation. A same trend of XRD peak intensity reversion depending on substrate temperature and an increase in Sn-doping concentration has also been reported in the literature [20,[26][27][28]. Zhao et al [20] and Gupta et al [26] showed temperature-dependent crystallite orientation change in Sn-doped CdO thin films prepared by MOCVD and pulsed laser deposition (PLD), respectively.…”
Section: Methodssupporting
confidence: 75%
See 1 more Smart Citation
“…Similarly, a small change in growth temperature can also change the crystallite orientation. A same trend of XRD peak intensity reversion depending on substrate temperature and an increase in Sn-doping concentration has also been reported in the literature [20,[26][27][28]. Zhao et al [20] and Gupta et al [26] showed temperature-dependent crystallite orientation change in Sn-doped CdO thin films prepared by MOCVD and pulsed laser deposition (PLD), respectively.…”
Section: Methodssupporting
confidence: 75%
“…Zheng et al [27] showed crystallite orientation change in PLD-prepared Sn-doped CdO thin films due to the variation in Sn-doping concentration. Ghosh et al [28] reported growth condition-dependent change in crystallite orientation of Sn-doped CdO synthesized by solution route. Figure 2 shows the XRD pattern of the films prepared using different volumes of cadmium acetate (0.05 M) and SnCl 4 (0.3 mM).…”
Section: Methodsmentioning
confidence: 99%
“…9 Subsequently, different dopants were introduced into In2O3, including, Ti, Sb, Ce and Mo, to tune to plasmon frequency from NIR to MIR. 12,[30][31] Many other types of metal oxides substitutionally doped with high-valence-cations have been extensively studied in the search of plasmonic semiconductor nanomaterials, including ZnO doped with Al, Ga, and In; 16 CdO doped with Dy, In, and Sn; 17,[32][33] TiO2 doped with Nb; 19 SnO2 doped with Sb, 18 etc. In these degenerately doped semiconductor NCs, the dopants substitute the lattice cations and cause the shift of the Fermi level depending on the energetic alignment of the dopant orbitals with the conduction band of metal oxides.…”
Section: N-type Plasmonic Semiconductor Ncsmentioning
confidence: 99%
“…Transparent conductive oxides (TCOs) are widely studied TCs. Whereas n ‐type TCOs, including substitutionally doped In 2 O 3 , SnO 2 , ZnO, and CdO, have already been applied in many modern devices, their p ‐type counterparts are rarely seen and have not been largely commercialized due to the p ‐type doping difficulty in wide‐gap oxides. Generally, the p ‐type doping difficulty in TCOs lies in the fact that their valence band maximum (VBM) with O‐2 p characters has a very low absolute energy, which is very difficult for p ‐type dopants to create shallow defect levels for good p ‐type doping performance .…”
Section: Introductionmentioning
confidence: 99%